2020
DOI: 10.3892/or.2020.7684
|View full text |Cite|
|
Sign up to set email alerts
|

lncRNA TTN‑AS1 upregulates RUNX1 to enhance glioma progression via sponging miR‑27b‑3p

Abstract: Long non-coding RNAs (lncRNAs) contribute to the tumorigeneses of numerous types of cancer, including glioma. The present study was designed to unveil a novel lncRNA functioning in glioma and explore the underlying mechanisms. lncRNA titin-antisense RNA1 (TTN-AS1), miR-27b-3p and Runt-related transcription factor 1 (RUNX1) expression in glioma tissues and cell lines was estimated by RT-qPCR. Si-TTN-AS1 was transfected into glioma cell lines (U251 and LN229), and CCK-8 assay, flow cytometry, wound healing and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…In this study, we revealed the carcinogenic function of RUNX1 in OSCC cells by regulating cell proliferation, cell adhesion, cell migration, and cell apoptosis. In addition, we found that RUNX1 was downstream of TTN-AS1, which is consistent with the study of Chang et al [ 45 ] in glioma cells that TTN-AS1 could regulated RUNX1 by sponging miR-27b-3p. However, we found that TTN-AS1 could sponge miR-199a-3p to enhance RUNX1 expression in OSCC, which is different from the study by Chang et al in glioma.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we revealed the carcinogenic function of RUNX1 in OSCC cells by regulating cell proliferation, cell adhesion, cell migration, and cell apoptosis. In addition, we found that RUNX1 was downstream of TTN-AS1, which is consistent with the study of Chang et al [ 45 ] in glioma cells that TTN-AS1 could regulated RUNX1 by sponging miR-27b-3p. However, we found that TTN-AS1 could sponge miR-199a-3p to enhance RUNX1 expression in OSCC, which is different from the study by Chang et al in glioma.…”
Section: Discussionsupporting
confidence: 93%
“…LncRNA TTN-AS1 has been stated and functionally confirmed to be involved in a variety of cancer progressions ( Chang et al, 2020 ; Feng et al, 2020 ; Lin et al, 2020 ; Miao et al, 2020 ; Qi and Li, 2020 ). Although the role of TTN-AS1 in BC is still poorly characterized.…”
Section: Resultsmentioning
confidence: 99%
“…TTN-AS1 and SNHG1 are lncRNAs that promote glioma development by upregulating RUNX1 [ 27 , 28 ]. Tang et al pointed out that TTN-AS1 induced malignant biological characteristics in glioblastoma cells via the miR-320b/EGR3/PKP2 axis [ 29 ].…”
Section: Discussionmentioning
confidence: 99%